2015
DOI: 10.1002/hed.23844
|View full text |Cite
|
Sign up to set email alerts
|

Salivary gland function after sialendoscopy for treatment of chronic radioiodine‐induced sialadenitis

Abstract: These results show that sialendoscopy can improve obstructive symptoms; however, it seems to have some limitations for relief of xerostomia and improvement of salivary gland dysfunctions in recalcitrant chronic radioactive iodine sialadenitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
63
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(66 citation statements)
references
References 20 publications
3
63
0
Order By: Relevance
“…More specifically, we directly visualized parotid ducts in RAI sialadenitis by sialendoscopy and found that RAI-damaged ducts showed findings such as bleached ductal walls, lumen stricture, and the impaction of mucous plugs and debris. 6 Degrees of ductal stricture also varied from edema with sialodochitis to severe stenosis. 6 Parotid gland impairment is usually more common than submandibular gland impairment after RAI therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, we directly visualized parotid ducts in RAI sialadenitis by sialendoscopy and found that RAI-damaged ducts showed findings such as bleached ductal walls, lumen stricture, and the impaction of mucous plugs and debris. 6 Degrees of ductal stricture also varied from edema with sialodochitis to severe stenosis. 6 Parotid gland impairment is usually more common than submandibular gland impairment after RAI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…6 Degrees of ductal stricture also varied from edema with sialodochitis to severe stenosis. 6 Parotid gland impairment is usually more common than submandibular gland impairment after RAI therapy. 17 In our study, grades of abnormal ductal and parenchymal findings were significantly higher for parotid glands than submandibular glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The parotid gland has a tendency to develop RAI sialadenitis earlier than the submandibular gland, even though NIS expression in the parotid glands does not exceed that in the submandibular gland [30]. This propensity is attributed to the higher clearance rate of salivary secretion in the submandibular glands [6, 10, 30]. We postulate that the effects of aromatherapy on submandibular gland damage are similar to those in the parotid glands; however, future studies are needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Saliva lubricates the oral mucosa, which allows proper speaking, swallowing, and tasting [5]. The prevalence of chronic RAI sialadenitis, an inflammation of the salivary glands, ranges from 11% to 67% after RAI therapy [611]. This condition causes pain and swelling which lead to oral discomfort [5, 7].…”
Section: Introductionmentioning
confidence: 99%